The Trickster in Appalachian and Hutsulian Tales - Derkachova, Olga; Ushnevych, Solomia (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The fairytales of Hutsuls and Appalachians are analyzed in the article. Mountainous dwellers have an indissoluble connection with the nature and metaphysics of mountains that is why there are so many sacred objects and special places there. Megaliths and sanctuaries, lifegiving places, miraculous springs, natural metaphysics of the mountains and tales which are grasped like true stories about creation and objective reality of the world, - all these attract not only tourists but also scientists and researchers to the mountainous region. The tale is one of the permanent attributes of people`s life. It gives the opportunity to make the process of emotional and moral development more controlled and determined. The common feature of the tale is identified: it is the presence of a hero-trickster - Jack (the Appalachians) and Ivan (the Carpathians). In tales, most of the fictional characters can be described by the term “duality”. It is a certain state of consciousness when the hero-character reproduces his double that lives an imaginary life and performs an intended role. It is a hero who is often hidden behind the mask of a jester and a foolish man. He does not live according to the rules. He breaks both laws and rules, but achieves positive results. The common and different features of the Trickster in the fairytales of Indians and Hutsuls are defined.